Research Center of Biochemistry and Molecular Biology, Xuzhou Medical College, Xuzhou 221002, China. - Hou Xiao-yu; Zhang Guang-yi (Acta Pharmacologica Sinica; Vol 20, No 11 (November 1999): Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of dopamine receptor antagonists on anoxia-induced inhibition of Ca(2+)-calmodulin dependent protein kinase II (CCDPK II) activity in rat hippocampus and striatum. METHODS: Using the rat hippocampal and striatal slices under 95% N2 + 5% CO2, the activity of CCDPK II was examined by 32P-incorporation. RESULTS: Under anoxia for 30 min, the CCDPK II activity decreased to 29.2% and 27.0% of the control in rat hippocampal and striatal slices, respectively. Preincubation with Sch-23390 (a specific D1-like dopamine receptor antagonist), or domperidone (a specific D2-like dopamine receptor antagonist), resulted in a concentration-dependent attenuation of the anoxia-induced inhibition of CCDPK II activity which was preserved up to about 60%. CONCLUSION: Dopamine receptor stimulation is involved in anoxia-induced inhibition of CCDPK II activity in rat hippocampus and striatum.